Preparation of β-Cyclodextrin Functionalized Platform for Monitoring Changes in Potassium Content in Perspiration - Liu, Ruixiang; Shi, Xiaofeng (Molecules (Basel, Switzerland), 2023)
The monitoring of potassium ion (K+) levels in human sweat can provide valuable insights into electrolyte balance and muscle fatigue non-invasively. However, existing laboratory techniques for sweat testing are complex, while wearable sensors face limitations like drift, fouling and interference from ions such as Na+. This work develops printed electrodes using β-cyclodextrin functionalized reduced graphene oxide (β-CD-RGO) for selective K+ quantification in sweat. The β-CD prevents the aggregation of RGO sheets while also providing selective binding sites for K+ capture. Electrodes were fabricated by screen printing the β-CD-RGO ink onto conductive carbon substrates. Material characterization confirmed the successful functionalization of RGO with β-CD. Cyclic voltammetry (CV) showed enhanced electrochemical behavior for β-CD-RGO-printed electrodes compared with bare carbon and RGO. Sensor optimization resulted in a formulation with 30% β-CD-RGO loading. The printed electrodes were drop-casted with an ion-selective polyvinyl chloride (PVC) membrane. A linear range from 10 μM to 100 mM was obtained along with a sensitivity of 54.7 mV/decade. The sensor showed good reproducibility over 10 cycles in 10 mM KCl. Minimal interference from 100 mM Na+ and other common sweat constituents validated the sensor’s selectivity. On-body trials were performed by mounting the printed electrodes on human subjects during exercise. The K+ levels measured in sweat were found to correlate well with serum analysis, demonstrating the sensor’s ability for non-invasive electrolyte monitoring. Overall, the facile synthesis of stable β-CD-RGO inks enables the scalable fabrication of wearable sensors for sweat potassium detection.